2011
DOI: 10.1128/jvi.00468-11
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic and Transcriptional Changes Which Follow Epstein-Barr Virus Infection of Germinal Center B Cells and Their Relevance to the Pathogenesis of Hodgkin's Lymphoma

Abstract: Although Epstein-Barr virus (EBV) usually establishes an asymptomatic lifelong infection, it is also implicated in the development of germinal center (GC) B-cell-derived malignancies, including Hodgkin's lymphoma (HL). Following primary infection, EBV remains latent in the memory B-cell population, where host-driven methylation of viral DNA contributes to the repression of viral gene expression. However, it is still unclear how EBV harnesses the cell's methylation machinery in B cells, how this contributes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
81
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 41 publications
7
81
1
Order By: Relevance
“…The apparent opposite effect of EBV on expression of DNMT1 and -3B in GC B cells (repression) and epithelial cells (activation) may reflect involvement of different cellular and/or viral factors. We note that the repression of DNMT1 and -3B in GC B cells (28) appears to be consistent with the lower level of these DNMTs in BL and LCL lines that maintain latency III relative to latency I BL lines, as observed here. Interestingly, following infection of GC B cells, DNMT3A could be detected within chromatin associated with Wp (but not Cp) (28), the EBNA promoter used prior to EBNA2 transactivation of EBNA expression from Cp.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The apparent opposite effect of EBV on expression of DNMT1 and -3B in GC B cells (repression) and epithelial cells (activation) may reflect involvement of different cellular and/or viral factors. We note that the repression of DNMT1 and -3B in GC B cells (28) appears to be consistent with the lower level of these DNMTs in BL and LCL lines that maintain latency III relative to latency I BL lines, as observed here. Interestingly, following infection of GC B cells, DNMT3A could be detected within chromatin associated with Wp (but not Cp) (28), the EBNA promoter used prior to EBNA2 transactivation of EBNA expression from Cp.…”
Section: Discussionsupporting
confidence: 61%
“…We note that the repression of DNMT1 and -3B in GC B cells (28) appears to be consistent with the lower level of these DNMTs in BL and LCL lines that maintain latency III relative to latency I BL lines, as observed here. Interestingly, following infection of GC B cells, DNMT3A could be detected within chromatin associated with Wp (but not Cp) (28), the EBNA promoter used prior to EBNA2 transactivation of EBNA expression from Cp. Most importantly, EBV-mediated induction of DNMT3A and its direct association with Wp, a latency gene promoter that undergoes methylation relatively early in infection (16) and which must ultimately be silenced to establish and maintain restricted latency, support the notion that methylation of the EBV genome is a regulated process.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Promoter hypomethylation of a number of proliferative genes was consistent with the conversion of resting B cells to proliferating blasts (26,27). EBV infection of germinal center B cells not only was shown to alter DNMT expression, resulting in changed DNA methylation patterns at particular regions, but also induced the histone 3 lysine 27 demethylase, KDM6B, potentially regulating genes differentially expressed in Hodgkin's lymphoma (28,29). However, in carcinoma cells, we previously demonstrated that EBV infection led to epigenetic silencing at the PYCARD and E-cadherin gene loci involving DNA methylation and repressive chromatin modifications, respectively (30).…”
mentioning
confidence: 94%